Role playing and augmented reality animal structures to support students' joyful learning and argumentation abilities - Arsyad, M.; Zaini, Muhammad; Kaspul, Kaspul; Ajizah, Aulia; Utami, Nurul Hidayati; Agustina, Noor Fithri; Azhari, Muhammad Hafizh (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2026)
Joyful learning is a strategy that can increase undergraduate student engagement and motivation in learning. This strategy is important for learning animal structures in biology students who have the potential to cause anxiety caused by treatment that is considered to be hurtful to animals. The use of role-playing and augmented reality (AR) technology in learning can provide a more interactive and interesting learning experience, thus providing opportunities for students to enjoy the learning process, as well as train their argumentation skills. The purpose of this study was to analyze the effect of role playing and augmented reality in the discovery learning model on joyful learning and students' argumentation skills. This study was a quasi-experimental study with a one-group pretest-posttest design. The research sample is undergraduate students in Biology Education department who are active in the odd semester of the 2025/2026 academic year and are taking the Animal Structure course. This design compared the conditions of joyful learning and argumentation skills before and after being given treatment in the form of learning Animal Structure topic using the discovery learning model, combined with role-playing assisted by augmented reality. The instruments of this study were a joyful learning questionnaire and an argumentation ability test instrument to collect quantitative data on joyful learning and argumentation skills. Data analysis used a nonparametric analysis of the Wilcoxon test because the data were not homogeneous and not normal. The results showed a significance value (Asymp. Sig. 2 tailed) of 0.00 (<0.05). The effect size on joyful learning was 0.87 and argumentation ability was 0.59. These results confirm that the integration of experience-based pedagogical strategies with immersive technology can create enjoyable learning while fostering students' critical thinking and argumentative skills.Abstrak. Joyful learning menjadi strategi yang dapat meningkatkan keterlibatan dan motivasi mahasiswa dalam pembelajaran, strategi ini penting untuk pembelajaran struktur hewan pada mahasiswa biologi berpotensi menimbulkan kecemasan. Penggunaan role playing dan teknologi augmented reality (AR) dalam pembelajaran dapat memberikan pengalaman belajar yang lebih interaktif dan menarik, sehingga dapat memberikan kesempatan kepada mahasiswa untuk menikmati proses belajar, serta melatih kemampuan argumentasinya. Tujuan penelitian ini untuk menganalisis pengaruh role playing dan augmented reality pada model discovery learning terhadap joyful learning dan kemampuan argumentasi mahasiswa. Penelitian ini merupakan penelitian kuasi eksperimen dengan desain one group pretest-posttest. Sampel penelitian terdiri dari mahasiswa program sarjana di Departemen Pendidikan Biologi yang aktif pada semester ganjil tahun akademik 2025/2026 dan sedang mengikuti mata kuliah Struktur Hewan. Desain ini membandingkan kondisi joyful learning dan kemampuan argumentasi sebelum dan sesudah diberikan perlakuan berupa pembelajaran Struktur Hewan dengan menggunakan model discovery learning yang dikombinasikan dengan role playing berbantuan augmented reality. Instrumen penelitian ini yaitu angket joyful learning dan instrumen tes kemampuan argumentasi untuk mengumpulkan data joyful learning dan kemampuan argumentasi secara kuantiatif. Analisis data menggunakan analisis nonparametrik uji Wilcoxon karena data tidak homogen dan tidak normal. Hasil penelitian menujukkan nilai signifikansi (Asymp. Sig. 2 tailed) sebesar 0,00 (<0,05). Hasil ini menegaskan bahwa integrasi strategi pedagogis berbasis pengalaman dengan teknologi imersif dapat menciptakan pembelajaran yang menyenangkan sekaligus menumbuhkan pemikiran kritis dan keterampilan argumentasi siswa.